CO-CULTIVATION OF TOMATO WITH TWO BACILLUS STRAINS: EFFECTS ON GROWTH AND YIELD - W. Akram; T. Anjum; B. Ali (Journal of Animal and Plant Sciences, 2015)
Plant growth promoting rhizobacteria (PGPR) have gained worldwide importance and acceptance for agricultural benefits. By virtue of their rapid rhizosphere colonization and stimulation of plant growth, there is currently considerable interest in exploiting these rhizosphere bacteria to improve crop production. In current investigation, two bacillus strains viz: Bacillus fortis IAGS162 and B. subtilis IAGS174 were evaluated for their ability to promote growth of three tomato varieties under greenhouse and field conditions. All the three tomato varieties were individually treated with both test bacterial strains in both greenhouse and field experiments. Experimentation was performed in completely randomized block design. In vitro biochemical assays indicated the ability of these bacteria to produce indole acetic acid, siderophores and phosphate solubilization. Greenhouse experiments indicated the ability of both strains to significantly increase shoot length, root length, and total biomass in all three tomato varieties. Seemly, significant increases in total chlorophyll, carotenoid and sugar concentrations were found in tomato plants co-cultivated with the bacterial strains. Two consecutive field experiments also supported the outcomes of the greenhouse assays. Tomato plants receiving bacterial inoculum had significantly greater shoot growth and fruit yield. B. subtilis IAGS174 was superior to B. fortis IAGS162 in promoting most traits studied in the laboratory or greenhouse. This study provided strong evidence for the potential use of these both bacterial strains in agriculture.
Keywords: Plant growth promoting bacteria (PGPB); Bacillus; Tomato; Indoleacetic acid; Phosphate solubilisation; Siderophores